DEVELOPMENT OF A PROTOTYPE OF MALARIA CLINICAL DIAGNOSTIC DECISION SUPPORT SYSTEM - Sudarta Yabesman Harefa; Lutfan Lazuardi; Anis Fuad (Pusat Kedokteran Tropis, 2011)
Introduction : Malaria is a public health problem that still causes mortality, particularly in high risk population. Kabupaten Nias is one of the malaria endemic areas. Malaria diagnosis is mainly determined according to physical examination, despite the fact that laboratory examination is the gold standard of malaria diagnosis. To help health workers in diagnosing malaria accurately, it is necessary to develop a decision support system for malaria diagnosis.Objectives: To develop a prototype of malaria diagnostic decision support system.Methods: It was a descriptive study with action research design to explore each phase in the development of a prototype of malaria diagnostic decision support system. Participants of the study consisted of 5 general practitioners in RSU Gunungsitoli and 2 nurses in Puskesmas Gunungsitoli.Results: The study created an application model of computer-based malaria diagnostic decision support system designed using PHP programming language and MySQL database. This system worked by entering malaria clinical symptoms into the expert system, and data of symptoms were processed by the expert system to determine diagnosis and medical advice that was useful to assist health staff in making decision.Conclusion: Malaria diagnostic decision support system that had been developed attracted the interest of health workers and help them in diagnosing malaria clinically.Keywords: diagnostic decision support system, prototype, malaria, computer application, Gunungsitoli